Association of Levels of Antepartum Angiogenic Factors with Severe Postpartum Hypertension [25I]. (May 2018) - Perdigao, Joana; Minhas, Ruby; Chintala, Sireesha; Mueller, Ariel; Young, Danielle; Rana, Sarosh
Abstract : INTRODUCTION: Postpartum hypertension often arises from an existing hypertensive disorder of pregnancy (HDP). Limited data exists about antecedent presentation and risk factors of PPHTN, especially among African American (AA) women. We studied the association between antepartum angiogenic biomarkers (sFlt1 and PlGF) and severe PPHTN among predominantly AA women. METHODS: Women with HDP were enrolled upon admission. Biomarkers were measured on an automated platform from maternal blood collected within 96 hours of delivery. PPHTN was severe if systolic blood pressure (SBP) ≥160 or diastolic blood pressure (DBP) ≥110 and mild if SBP ≥140 or DBP ≥90. Descriptive statistics were assessed with a Wilcoxon Rank Sum or chi-square test, as appropriate. Univariate and multivariable logistic regression was used to assess the association between PPHTN and angiogenic factors, reporting the area under the receiver operating curve (AUC). RESULTS: 375 women were enrolled, with 279 (74.4%) AA and 151 (40.3%) with severe PPHTN. 52.9% of women with severe PPHTN also had antepartum pre-eclampsia with severe features. The sFlt1/PlGF ratio was significantly higher for both severe and mild PPHTN compared to women with normal postpartum BPs (73.5, 46.0 and 13.0 respectively, p<0.0001). Furthermore, the highest tertile of antepartum sFlt1/PlGF ratio was associated with severe PPHTN [OR 2.52, 95% CI: 1.49-4.27; p=0.001] which persisted after adjustment [OR 2.83; p=0.001]. When predicting severe PPHTN, the adjusted AUC for sFlt1/PlGF was 0.71. CONCLUSION: A significant association exists between antepartum angiogenic biomarkers and severe PPHTN — a frequent manifestation in women with antepartum HDP. Further studies should evaluate the mechanisms of such association.